2014
DOI: 10.1007/s11590-014-0758-2
|View full text |Cite
|
Sign up to set email alerts
|

For the airplane refueling problem local precedence implies global precedence

Abstract: We are given n airplanes, which can refuel one another during the flight. Each airplane has a specific tank volume and gas consumption rate. The goal of the airplane refueling problem is to find a drop out permutation for the planes that maximizes the distance traveled by the last plane to drop out. This paper studies some structural properties of the problem and proposes pruning rules for an exact resolution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…For example Höhn and Jacobs (2012a) showed that if β = 2 and p i ≤ p j then i ≺ g j if and only if i ≺ j. The same characterization has been shown for a related objective function, where one wants to maximize w j C −1 j (Vásquez 2014). This situation motivates us to state the following conjecture.…”
Section: Our Contributionmentioning
confidence: 72%
“…For example Höhn and Jacobs (2012a) showed that if β = 2 and p i ≤ p j then i ≺ g j if and only if i ≺ j. The same characterization has been shown for a related objective function, where one wants to maximize w j C −1 j (Vásquez 2014). This situation motivates us to state the following conjecture.…”
Section: Our Contributionmentioning
confidence: 72%
“…Latter, Bansal et al [4] confirmed this conjecture, and they also gave a counter example of the generalized conjecture that i ≺ l[a,b] j implies i ≺ g[a,b] j. For airplane refueling problem, Vsquez [17]…”
Section: Related Workmentioning
confidence: 93%
“…⊓ ⊔ Dominance rule Vsquez [17] proved the following dominance properties of airplane refueling problem.…”
Section: Preliminariesmentioning
confidence: 99%
See 2 more Smart Citations